SISTEM INFORMASI STOK KAYU PADA CV. CONTA DORA: Information System;Stock;Visual Basic 6.0;Access;Crystal Report. - Afrizal; Afri Hajiansyah , Thendy (FORTECH (Journal of Information Technology), 2021)
Conta Dora is an independent business engaged in saw wood in Pasir Pajang village. for now, the data on wood stock is still done manually. In this study, a visual basic 6.0-based system was designed. With this system, it is expected to be able to overcome user needs for things in stock counting and report generation. From this research that has been carried out the author implements the results of these studies into the Design of Information Systems, Design of wood stock information systems on Cv. Conta Dora was built using Visual Basic 6.0, Crystal reports and Microsoft Access databases.With the design of a wood stock information system, it can help and simplify the data processing process on Cv. Conta Dora, Especially in the entry of wood stock and exit of wood stock.